Pemanfaatan Online Platform dalam Pembelajaran Teknik Informatika - Hidayatullah, Syarif; Murni, Abdul Aziz Amir; Muhammad, Muhammad (MASALIQ, 2023)
The aim of this article is to elucidate the benefits of utilizing online platforms in the teaching of information technology. We summarize the key findings within this article, encompassing crucial aspects such as global accessibility, learning flexibility, interactive education, global collaboration, content quality, and the comprehension of ethics and cybersecurity. The method employed in this article is a literature review and understanding based on current research and practices in information technology education. We gathered information from various relevant sources and compiled it into a comprehensive summary.This article synthesizes the foremost advantages of employing online platforms, provides examples of successful implementation, and addresses the challenges faced within the realm of information technology education. The conclusion drawn is that the utilization of online platforms in information technology education yields significant positive impacts, facilitating global access, fostering flexibility, promoting interactive learning, encouraging global collaboration, ensuring content quality, and enhancing cybersecurity awareness. The future of education in this field will continue to be interconnected, open, and responsive to technological advancements. This transformation brings about substantial positive changes in how we learn and teach.